Analysis of the Application of the Principle of Social Function of Land Rights and the Legal Position of Property Rights in a Social Context (CASE STUDY OF DECISION NUMBER 1273/PDT.G/2023/PN TNG) - Cahyaning Putri Kinasih (Annual Review of Legal Studies, 2025)
The principle of the social function of land rights is a fundamental concept in Indonesian agrarian Law, as stipulated in Article 6 of the Basic Agrarian Law (UUPA). This study aims to analyze the implementation of this principle in judicial decisions, specifically Decision Number 1273/PDT.G/2023/PN TNG, and its implications for the legal status of Land Ownership Certificates (SHM). Using a normative-juridical approach and case study method, this article examines the conflict between individual interests of SHM holders and the broader social interests of the community. It also evaluates the extent of legal protection afforded to landowners amidst rapid urban development. The analysis reveals that the application of the social function principle often encounters practical obstacles, such as low legal awareness and weak enforcement of agrarian norms. The study highlights the need for regulatory reinforcement and improved public legal literacy to ensure social justice in land utilization.